Structure and Magnetization of Strontium Hexaferrite (SrFe12O19) Films Prepared by Pulsed Laser Deposition - Khojaste khoo, M.; Kameli, P. (Frontiers in Materials, 2021)
M-type strontium hexaferrite (SrM) thin films show excellent magnetic properties and uniaxial magnetic anisotropy. We systematically investigated the magnetism of SrM films prepared by pulsed-laser deposition on different substrates [Al2O3 (11¯02), SrTiO3 (100), ZnO (0001), and LiNbO3 (0001)] at vacuum (10−4 Pa) and a substrate temperature of 800°C. Prepared films were annealed in air at a temperature of 1,000°C for 2 hours. This investigation determined the effect of annealing and different substrates on the morphology, strain, and hysteresis loops of the films. The prepared films were characterized using x-ray diffractometry, Raman spectroscopy, scanning electron microscopy, and superconducting quantum interference device (SQUID) magnetometry. X-ray diffraction analyses confirmed c-oriented growth along the out-of-plane direction in most films. We found that annealing causes enhanced crystallization in films and a significant increase in coercivity. The highest coercivity of ∼11 KOe was measured for the film deposited on the Al2O3 (11¯02) substrate.